Calculation of the Best Date for Transfer Orbit withPerturbation from (GTO) to Lagrange Point (L2) - Fadhil, Omar A.; Saleh, Abdul-Rahman H. (Iraqi Journal of Science, 2025)
Lagrange points are points where the gravity of two large celestial bodies does not affect a third body, usually smaller, making its motion follow the motion of the two large bodies. There are five points relative to the Earth, the Sun, and any third body, such as a satellite or a spacecraft. Three essential points are usually symbolized as L1, L2, and L3. This research aims to calculate the best date in 2025 for the satellite to transition from the GTO orbit to the L2 Lagrange point, another transition station to transfer the satellite from (L2) to the Mars orbit. A program was designed in MATLAB to calculate the best date 2025 for the satellite to transition from the Geosynchronous Transfer Orbit (GTO) to the L2 Lagrange point during a transition orbit between the Earth orbit (GTO) to the Sun orbit L2. This requires reaching the escape velocity from the Earth orbit and then the extinction velocity when the spacecraft arrives near L2 in the presence of three types of perturbations: solar gravitational perturbation, the effect of the third body, and the perturbation of the Earth's non-sphericity J2. The results showed that the best date for the transition is Monday, October 2, 2025, because the required velocity for the transition is suitable. The perturbation effect on the orbital elements is small compared to other dates. The transition time is 35.34 days. This means that the departure day will be Monday, Monday, October 2, 2025, and the arrival will be Monday, March 17, 2025. Although there are other dates for the satellite transition with the shortest transition time, the perturbation on the orbital elements of the transition orbit is higher. The perturbation effect on the orbital elements of the transition orbit depends on the satellite's mass. The greater the satellite's mass, the less the effect of perturbation on it, and vice versa.